2020
DOI: 10.1186/s12302-020-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

Rational synthesis, characterization, and application of environmentally friendly (polymer–carbon dot) hybrid composite film for fast and efficient UV-assisted Cd2+ removal from water

Abstract: Background Carbon dots (CDs) are of particular interest in numerous applications. However, their efficiency for heavy metal removal from wastewater was not yet reported. Herein, we rationally synthesized CDs from petroleum coke waste via hydrothermal treatment in the presence of ammonia. Results This drove the formation of outstanding photoluminescent, water-soluble, biocompatible, and high yield of monodispersed sub-5 nm CDs. The CDs are co-doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 71 publications
5
48
0
Order By: Relevance
“…However, its chemical sensitivity and poor mechanical properties limited its industrial uses. Nevertheless, many previous studies confirmed that the incorporation of PPy with other polymers, nanoparticles, or biobased materials such as cellulose or clay minerals [22] was found to improve the PPy stability and sensitivity [23,24]. Previous studies, in our team described the preparation of low-cost and conductive clay-PPy nanocomposites, with enhanced antibacterial, catalytic properties [24][25][26].…”
Section: Introductionmentioning
confidence: 75%
“…However, its chemical sensitivity and poor mechanical properties limited its industrial uses. Nevertheless, many previous studies confirmed that the incorporation of PPy with other polymers, nanoparticles, or biobased materials such as cellulose or clay minerals [22] was found to improve the PPy stability and sensitivity [23,24]. Previous studies, in our team described the preparation of low-cost and conductive clay-PPy nanocomposites, with enhanced antibacterial, catalytic properties [24][25][26].…”
Section: Introductionmentioning
confidence: 75%
“…The O 1 s spectrum ( Figure 3c) showed two peaks at 530.7 and 531.9 eV corresponding to O-H and C=O, respectively. It is worth noting that the incorporation of active moietises including N-H and C=O can effectively enhance the QY of CDs, which provide more active sites for capturing a variety of analytes [4,13,48]. The corresponding elemental compositions (in atomic ratios) are summarized Table S1.…”
Section: Chemical Structurementioning
confidence: 99%
“…According to the Disease Registry and Environmental Protection Agency (EPA), Cd(II) ranks seventh on the top 20 toxic chemicals priority list [3]. Long-term exposure to Cd(II) results in a series of harmful diseases in humans ecosystem damage [4]. Due to its toxic effects on human health, the separation and elimination of Cd 2+ from aquatic media is still a hot research topic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations